Strategic SWOT analysis of public, private and not-for-profit festival organisations - Carlsen, Jack; Andersson, T. (Emerald Group Publishing Limited, 2011)
Purpose: This analysis relates to the strategic orientation of public, private and not-for-profit festivals and the adoption of stakeholder, financial, marketing and management strategies that enable them to achieve their organisational objectives. The paper aims to address these issues. Design/methodology/approach: In order to test the effectiveness of this new strategic SWOT approach, data from the four-country study of festivals were employed to investigate how a strategic approach can be adopted by festival managers in the public, private and not-for-profit sector. The strategic issues that confront all festivals, including, financial management and related issues of costs, revenue, sponsorship and support are the subject of analysis. Findings: The findings indicate that among festival managers there are some interesting and significant differences between the three ownership types in terms of their strengths, weaknesses, opportunities and threats. Private and non-profit festivals are comparatively more strategic in responding to financial opportunities, threats and weaknesses and public festivals are more dependent on a single stakeholder and source of revenue. Other significant differences exist in terms of stakeholder management and sponsorship strategies, which can be explained with reference to resource dependency theory.Research limitations/implications: Strategic SWOT analysis can provide a more rigorous and structured approach to researching the multiple challenges that festival managers face and the strategies they adopt. This paper demonstrates that it has some utility in identifying strategies in response to financial, stakeholder and sponsorship imperatives. Practical implications: Strategic SWOT analysis provides event and festival managers with a new tool for understanding the range of challenges and opportunities that they can address through adopting a more strategic response. Originality/value: The field of festival and event management studies is largely devoid of any literature with reference to analysis of strategies that different festivals adopt in response to identified weaknesses, opportunities and threats. This paper provides new insights into the strategic management of public, private and not-for-profit festival organisations using an original approach and an extensive four-country dataset.